MULTIMODAL HUMOUR ON OVERPOPULATION IN JOEL PETT’S ENVIRONMENTAL CARTOONS - Živilė Nemickienė; Dovilė Urbonienė; Julija Zabielinaitė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Cartoonists’ skill to reveal important problems, to influence and construct public opinion has become a great power. This study examines humour as a social instrument and focuses on the expression of humour, or irony in particular, in famous American cartoonist Joel Pett’s overpopulation cartoons. The analysis explores the role, interaction and synergic effect of verbal and visual modes in constructing an ironic attitude towards the negligence of urgent global issues. Four selected Joel Pett’s environmental cartoons are analysed in detail, examining their content, the incongruity between the implied and explicit messages, the verbal mode and its interplay with the pictorial signs, and the amusing effect which is achieved by multimodality. The message communicated via visual mode contributes to the context of the cartoon, helping the reader comprehend the implications, and correlates with the verbal means rendering its hilarious message. Multimodality is determined as an essential element that allowed the reader to perceive humour.